2006
DOI: 10.1532/ijh97.05111
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate Mofetil Is Effective and Well Tolerated in the Treatment of Refractory Acute and Chronic Graft-versus-Host Disease

Abstract: We enrolled 11 patients with refractory graft-versus-host disease (GVHD) in a prospective trial evaluating the efficacy of mycophenolate mofetil (MMF). Four (67%) of the 6 patients with acute GVHD and all 5 patients with chronic GVHD responded to MMF. Ten (91%) of the 11 patients were able to decrease steroid use (median decrease, 86%; range, 25%-100%). After a median follow-up of 18 months (range, 1-65 months), 7 patients (64%) remained alive. The adverse events were infectious complications (36%), diarrhea (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 28 publications
1
23
0
2
Order By: Relevance
“…[6][7][8][9][10][11][12][13][14][15] Moreover, the tolerability of MMF and ease of oral administration for prolonged periods of time made MMF an attractive alternative among other agents that could have been tested for efficacy in the initial treatment of chronic GVHD. Several hypothetical a priori explanations could be considered as possibly accounting for an (14) .07…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8][9][10][11][12][13][14][15] Moreover, the tolerability of MMF and ease of oral administration for prolonged periods of time made MMF an attractive alternative among other agents that could have been tested for efficacy in the initial treatment of chronic GVHD. Several hypothetical a priori explanations could be considered as possibly accounting for an (14) .07…”
Section: Discussionmentioning
confidence: 99%
“…Instead, the study was based on results of previous reports suggesting the efficacy of MMF for treatment of steroid-refractory chronic GVHD, [6][7][8][9][10][11][12][13][14][15] and the proposed effect size was based on the number of patients who could be enrolled in a multicenter study within a reasonable period of time. Even so, the negative results of this study did not simply reflect an overstringent primary endpoint or an unrealistic effect size because the much less stringent endpoint of complete response also did not show an advantage for the MMF arm.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33][36][37][38] Direct comparisons to other series examining MMF in refractory GVHD are difficult for several reasons. Basara et al reported an overall grade improvement in 65% of patients, where MMF was used as first-line therapy in addition to CSA and prednisolone on development of aGVHD or cGHVD.…”
Section: Discussionmentioning
confidence: 99%
“…The nationwide survey of ATG as second-line therapy for acute GVHD is ongoing. Takami et al [129] evaluated the outcomes of patients who were treated with MMF at a dosage of 1500 mg/ day in a prospective study. Onishi et al [130] retrospectively analyzed the outcome of patients who received MMF at an initial dose of 500-3000 (median 1500) mg/day.…”
Section: Second-line Therapy Of Acute Gvhdmentioning
confidence: 99%